Capital structure in large Malaysian companies - Mohamad, Mohamad Hanapi (Wiesbaden: Gabler Verlag, 1995)
This paper attempts to examine the determinants of firms' capital structure in Malaysia covering the period between 1986 to 1990. A discussion on the capital structure behaviour in the Malaysian financial market implies that there are similarities between developed and less developed financial markets,involving the influences of firms' capital structure. Specifically, a firm's size and industry class play a significant role in determining a firm's capital structure.